2006
DOI: 10.1002/jmri.20822
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance voiding cystourethrography for vesicoureteral reflux

Abstract: Purpose:To assess the feasibility of magnetic resonance voiding cystourethrography (MRVCUG) using MR fluoroscopy for evaluation of vesicoureteral reflux (VUR), and its use as a noninvasive alternative to standard VCUG. Materials and Methods:A total of 22 MR studies of 16 patients (five months to 41 years old) with primary VUR diagnosed by standard VCUG were evaluated. Six patients underwent MR studies and standard VCUG pre-and postoperatively. MR fluoroscopy was executed with a non-enhanced heavily T2-weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Our sample size of 12 patients is small, but adequate to demonstrate feasibility, and comparable to previous MRIbased studies of VUR (6 to 20 subjects [12][13][14][15]). Some previous MRVC studies only examined children with known VUR, from which no sensitivity data can be obtained, unlike our study [13].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Our sample size of 12 patients is small, but adequate to demonstrate feasibility, and comparable to previous MRIbased studies of VUR (6 to 20 subjects [12][13][14][15]). Some previous MRVC studies only examined children with known VUR, from which no sensitivity data can be obtained, unlike our study [13].…”
Section: Discussionmentioning
confidence: 80%
“…For MR imaging, this group is likely to be the hardest group to image in terms of signal-to-noise ratio and identifying small moving structures, but may yield fewer motion artefacts when compared with slightly older children. No previous study using MR to identify VUR has concentrated solely on the neonatal population (average ages 3 -10 years; [11][12][13][14]). Our study avoided the use of sedation [13,14], and demonstrates feasibility on a conventional closed bore MR system [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Takazakura et al [41] confirmed the diagnostic accuracy of MRVCUG compared to traditional VCUG. They compared 44 renal units, all of which were imaged both with MRVCUG and VCUG within a period of less than 1 month.…”
Section: Magnetic Resonance Voiding Cystogramsmentioning
confidence: 71%